The Stacks project

Lemma 10.97.1. Let $A$ be a ring. Let $I \subset A$ be an ideal. Let $(M_ n)$ be an inverse system of $A$-modules. Set $M = \mathop{\mathrm{lim}}\nolimits M_ n$. If $M_ n = M_{n + 1}/I^ nM_{n + 1}$ and $I$ is finitely generated then $M/I^ nM = M_ n$ and $M$ is $I$-adically complete.

Proof. As $M_{n + 1} \to M_ n$ is surjective, the map $M \to M_1$ is surjective. Pick $x_ t \in M$, $t \in T$ mapping to generators of $M_1$. This gives a map $\bigoplus _{t \in T} A \to M$. Note that the images of $x_ t$ in $M_ n$ generate $M_ n$ for all $n$ too by Nakayama's lemma (Lemma 10.19.1). Consider the exact sequences

\[ 0 \to K_ n \to \bigoplus \nolimits _{t \in T} A/I^ n \to M_ n \to 0 \]

We claim the map $K_{n + 1} \to K_ n$ is surjective. Namely, if $y \in K_ n$ choose a lift $y' \in \bigoplus _{t \in T} A/I^{n + 1}$. Then $y'$ maps to an element of $I^ n M_{n + 1}$ by our assumption $M_ n = M_{n + 1}/I^ nM_{n + 1}$. Hence we can modify our choice of $y'$ by an element of $\bigoplus _{t \in T} I^ n/I^{n + 1}$ so that $y'$ maps to zero in $M_{n + 1}$. Then $y' \in K_{n +1}$ maps to $y$. Hence $(K_ n)$ is a sequence of modules with surjective transition maps and we obtain an exact sequence

\[ 0 \to \mathop{\mathrm{lim}}\nolimits K_ n \to \left(\bigoplus \nolimits _{t \in T} A\right)^\wedge \to M \to 0 \]

by Lemma 10.86.1. Fix an integer $m$. As $I$ is finitely generated, the completion with respect to $I$ is complete and $(\bigoplus _{t \in T} A)^\wedge / I^ m(\bigoplus _{t \in T} A)^\wedge = \bigoplus _{t \in T} A/I^ m$ (Lemma 10.95.3). We obtain a short exact sequence

\[ (\mathop{\mathrm{lim}}\nolimits K_ n)/I^ m(\mathop{\mathrm{lim}}\nolimits K_ n) \to \bigoplus \nolimits _{t \in T} A/I^ m \to M/I^ mM \to 0 \]

Since $\mathop{\mathrm{lim}}\nolimits K_ n \to K_ m$ is surjective we conclude that $M/I^ mM = M_ m$. It follows in particular that $M$ is $I$-adically complete. $\square$

Comments (4)

Comment #4730 by Hammerhead on

Not really sure why the images of generate the . Could this be elaborated? In any case, why not just choose the to be generators of instead? Then the images of seem to generate the due to surjectivity of . Did I miss something?

Comment #4731 by on

OK, we should add a reference to Nakayama's lemma 10.19.1 or we should do what you said.

Comment #4990 by Tongmu He on

I would like to give an another proof of lemma 10.97.1.

(1) First, if we only require that and is finitely generated, let's show that is -adically complete: We have . Taking limit, we get . Hence is a direct summand of . By lemma 10.95.3, is -adically complete, so is .

(2) If moreover , let's show that : Consider short exact sequence . Notice that is killed by . Therefore, by Nakayama's lemma 10.19.1, is surjective. On the other hand, (1) shows that . We conclude that and thus .

Post a comment

Your email address will not be published. Required fields are marked.

In your comment you can use Markdown and LaTeX style mathematics (enclose it like $\pi$). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).

Unfortunately JavaScript is disabled in your browser, so the comment preview function will not work.

All contributions are licensed under the GNU Free Documentation License.

In order to prevent bots from posting comments, we would like you to prove that you are human. You can do this by filling in the name of the current tag in the following input field. As a reminder, this is tag 09B8. Beware of the difference between the letter 'O' and the digit '0'.